Depression Among Medical Students at West Bank Universities - Idkedek, Mayar; Moreb, Beesan; Sharif, Niveen; Rishiq, Aseel; Hliqawi, Alaaeddin; Idkaidak, Sara; O. Khalil, Mohammad; Hamad, Lana; Hallak, Hussein (Jordan Medical Journal, 2024)
This study investigated the propensity for medical students to experience symptoms of depression, relative to other students, at West Bank Palestinian universities. In addition, the study evaluated the socio-demographic or academic factors that might influence this propensity. A quantitative, cross-sectional study was conducted on 714 medical and non-medical students from Al-Quds and Al-Najah Universities. Data were generated through a questionnaire that included sociodemographic parameters and academic status, and measured depression using the Beck Depression Inventory. The data were analyzed using SPSS (v. 20). About a third of the sample’s medical students suffered from some form of depression. Moderate depression appeared to be relatively high among medical (18.7%) and non-medical students (25.5%). At all depression levels, there was a significantly lower prevalence of depression among medical students compared to non-medical, with the exception that the medical students suffered a higher rate of mild mood disturbances (25.1%) than the non-medical (14.6%). Furthermore, there were significant correlations (α ≤0.05) between a higher prevalence of depression and being female, lower grade point average (GPA), lower economic status, and a lack of psychological support. Other variables, such as accommodation and year of study, showed insignificant relationships with depression. Depression was highly prevalent among the students, regardless of their university or field of study, which probably reflects the high depression rates in the wider Palestinian society. Nevertheless, the lower prevalence of depression among the medical students may be attributed to the fact that higher quality students are accepted by medical schools and their level of adaptation to stress and hard work. Finally, our results challenge the perception of a higher depression rate among medical students.